Virtual Input Devices For Underwater Manipulator. - Nordin, Nadira; Soori, Umair; Arshad, Mohd Rizal (2008)
Computer vision gives the potential to present a vision-based hand tracking system for virtual input. Tracking hand movement has become popular, efficient and more natural in human computer interaction.